2019
DOI: 10.1016/j.molcel.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Single-Nucleotide Precision of Primary microRNA Processing

Abstract: Highlights d The mGHG motif can dictate the cleavage site with singlenucleotide precision d Processing site of primary microRNA is determined by DROSHA rather than DGCR8 d The dsRBD of DROSHA recognizes the mGHG motif

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 50 publications
6
104
0
Order By: Relevance
“…This strengthens the interaction between DROSHA and the junction, and thus enhances its cleavage efficiency and accuracy 13,21 . In addition, DROSHA has a double-stranded RNA binding domain (dsRBD), which it uses to interact with an mGHG motif located in the lower stem of the pri-miRNA to precisely find the correct cleavage sites 18,22 . DGCR8 in a dimer form also plays an essential role in ensuring that DROSHA cleaves accurately~22 nt from the apical junction.…”
mentioning
confidence: 99%
“…This strengthens the interaction between DROSHA and the junction, and thus enhances its cleavage efficiency and accuracy 13,21 . In addition, DROSHA has a double-stranded RNA binding domain (dsRBD), which it uses to interact with an mGHG motif located in the lower stem of the pri-miRNA to precisely find the correct cleavage sites 18,22 . DGCR8 in a dimer form also plays an essential role in ensuring that DROSHA cleaves accurately~22 nt from the apical junction.…”
mentioning
confidence: 99%
“…Previous studies have employed screening of libraries of miRNA sequences to identify features that improved Drosha and Dicer cleavage. This has led to the identification of primary sequence motifs including CNNC, GHG, and GUG, present in flanking regions and loops, respectively, that improve Drosha binding and cleavage (Auyeung et al 2013;Fang and Bartel 2015;Kwon et al 2019). We wanted to identify features that improve the entire biogenesis pathway, and avoid Ago2 slicing of the stem, to maximize target knockdown potential.…”
Section: Resultsmentioning
confidence: 99%
“…However, the overall goal of our study is to model single-copy shRNA potency, and high copy shRNA expression might favor different structural features. Previous studies have used libraries of artificial miRNA sequences to probe Drosha and Dicer processing motifs (Auyeung et al 2013;Fang and Bartel 2015;Kwon et al 2019). These studies were designed to capture and identify the library RNAs without the background of endogenous miRNAs, allowing complete saturation of the screen.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that deviations from the expected cleavage site between the basal junction and the apical junction of a pri-miRNA can result in alternative cleavage by Drosha 27 . Furthermore, structural defects affect imprecise Drosha cleavage in the lower stem, altering the overall helical structure of the pri-miRNA, as well as disrupting the interaction between Drosha and the sequence motif of the lower stem 28 . RNA-binding proteins such as hnRNPA1 control Drosha cleavage by changing the secondary structure of the pri-miRNA, which might be one of the reasons why such proteins regulate alternative cleavage by Drosha 29 .…”
Section: Mirna Heterogeneitymentioning
confidence: 99%